Looking Around – A New Set of Textual Material in Environmental Studies for Class III - Jain, Manju (THE PRIMARY TEACHER, 2006)
When we think of General Science and Social Studies in primary classes, we clearly have in mind some ‘body of knowledge’ and also ‘typical ways of acquiring’ that knowledge. Such an approach naturally tends to think of topics that have traditionally served as the basis of their own disciplines. In the last few decades, it has been increasingly seen that children learn holistically rather than in a compartmentalised manner, i.e., concepts of science, geography, history, etc. through a disciplinary approach. It has also been proved that children not only learn through interaction with the environment, but also through talking, discussing, and interacting with other people, both adults and children. With an appropriate question or suggestion, the child’s understanding can be extended far beyond the point which she could have reached alone. The new EVS syllabus and textual material is developed within this ‘social constructivist’ perspective of learning. The EVS syllabus consciously begins with key questions rather than key concepts. This is to trigger the child’s thinking in new directions and provide a scaffolding to her learning process. With this aspect in view, the NCF-2005 recommends that Environmental Studies be taught as an integrated course for the entire primary stage instead of two distinct parts, i.e., Science and Social Studies.